Hot spot identification and mitigation at strategic level by subliminal changes in aircraft time of arrival at junction - Gatsinzi, Dany; Saez Nieto, Francisco Javier; Madani, Irfan (Eurocontrol, 2016)
This paper presents some results obtained when applying a different criterion in Air Traffic Flow and Capacity Management (ATFCM) measures. The approach is based on reducing the probability of controller’s reactive interventions by "hot spot" identification and mitigation at strategic level, by applying subliminal changes on the aircraft’s Times of Arrival (TOA) at the crossing or merging points (junctions). The concept of this strategy is fully aligned with the Trajectory Based Operation (TBO) principles. It is assumed that the changes on the times of arrival only demand very small speed changes to the involved aircraft (A/C). In this assessment, hot spots are established by identifying groups of closely spaced A/C arriving at a junction. A hot spot isolates the set of A/C involved in multiple conflicts, close in their times of arrival at the junction, violating the minimum required “safe” time separation at the junction. The minimum safe time separation is established based on a chosen threshold for the probability of collision obtained by considering the different sources of uncertainties in the aircraft’s time of arrival at junction. Some exercises are proposed and solved by applying this method. The obtained results show its ability to remove the conflicts by applying simple linear optimization programming tool. The effect of this method on the aircraft’s operating costs is also analyzed. This approach also seeks to change the current capacity-limiting factor, established by the number of aircraft occupying simultaneously each sector, to another parameter where the level of traffic complexity, flowing towards junctions, will be identified and mitigated at strategic level.
Keywords: ATFCM; TBO; CD&R; DCB; junction; TOA; hot spot; complexity; operating costs